Design of antibacterial polyethylene terephthalate masterbatch functionalized by modified nano‐Mg(OH)2. Issue 46 (9th September 2018) - Zhu, Yimin; Wang, Ying; Sha, Lin; Zhao, Jiao; Li, Xiaoyi
ABSTRACT: In this work, antibacterial polyethylene terephthalate (PET) masterbatch (APM) was prepared by melting‐and‐mixing technology, with nano‐Mg(OH)2 as antibacterial fillers and pure‐PET slices as basic materials. In addition, titanate coupling agents and stearic acid were used as additives to improve the compatibility of nano‐Mg(OH)2 and PET. The scanning electron microscope (SEM) characterization indicated that the modified nano‐Mg(OH)2 particles (10, 20, and 30%) wrapped by PET with a diameter ranging of 0.1–0.5 μm were well dispersed in APM. Moreover, the attenuated total reflectance Fourier transform infrared spectroscopy (ATR‐FTIR) results indicated the existence of titanate coupling agents and stearic acid in APM. Furthermore, the antibacterial test showed that nano‐Mg(OH)2 and APM had excellent antibacterial property against Escherichia coli ( E. coli ) and resulted in the protein leakage of E. coli . © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46755. Abstract :